Mainstreaming the right-wing radicalism and extremism: basic approaches and perceptions from Georgian academia - Tabatadze, Sandro; Dundua, Salome (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Unlike some European countries, the involvement of radical right-wing forces in Georgian politics and the support of a certain part of the society for them is a relatively new phenomenon in Georgia`s politics. This has resulted in a growing interest in the study of the topic among Georgian academic circles. However, the defining and applying the concepts of radicalism and extremism regarding Georgian right-wing forces are different. By comparing the major approaches to the concepts of right-wing radicalism and extremism this paper aims to critically review and analyze perceptions from Georgian academia.
Keywords: Georgia; far-right; radical right; Euroscepticism; Georgian academia